2013
DOI: 10.1002/cbf.2987
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in circulating angiogenic and anti‐angiogenic factors in type 2 diabetic patients with neuropathy

Abstract: Diabetic peripheral neuropathy (DPN) is one of the most common diabetic chronic complications. There is an increased attention directed towards the role of angiogenic factors including vascular endothelial growth factor (VEGF) and anti-angiogenic factors including soluble endoglin (sEng) as contributors to diabetic microvascular complications including neuropathy. The purposes of this study were to determine the role of these angiogenesis regulators in the prognosis of DPN. The study group included 60 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
3
14
0
Order By: Relevance
“…Several studies reported that diabetic individuals display relatively increased serum levels of proangiogenic factors [30,31,32]. In our study exclusively VEGF and bFGF serum levels in the diabetic statin-free group were significantly higher compared to the nondiabetic statin-free control group, while in the statin-treated group of patients with type 2 diabetes examined proangiogenic factors did not differ to the control group.…”
Section: Discussionsupporting
confidence: 43%
“…Several studies reported that diabetic individuals display relatively increased serum levels of proangiogenic factors [30,31,32]. In our study exclusively VEGF and bFGF serum levels in the diabetic statin-free group were significantly higher compared to the nondiabetic statin-free control group, while in the statin-treated group of patients with type 2 diabetes examined proangiogenic factors did not differ to the control group.…”
Section: Discussionsupporting
confidence: 43%
“…Similar results were obtained by Motawi [ 7 0 _ T D $ D I F F ] et al [39]. It seems likely that the increased VEGF serum level may be a compensatory mechanism occurring in patients with diabetic neuropathy allowing healing of nerves [ 7 1 _ T D $ D I F F ] [40].…”
Section: Discussionsupporting
confidence: 85%
“…In accordance with recent studies [8, 18-20], through measuring plasma levels of VEGF, IL-1β, IL-6, TNF-α, and TLR4 we found that inflammatory factors and VEGF expression were higher in patients with DPN than in DN patients. These findings are in agreement with the theory that DPN may be associated with inflammation and endothelial dysfunction [21].…”
Section: Discussionsupporting
confidence: 70%